SISTEM INFORMASI PENJADWALAN PROYEK MENGGUNAKAN METODE PERT (PROGRAM EVALUATION AND REVIEW TECHNIQUE) DI CV. INFOTECHMEDIA - Yus Jayusman; Murlinah; Ogi Rizki Fadillah (Jurnal Teknologi Informasi dan Komunikasi, 2022)
CV. Infotech Media is a legally established national private company specializing in website, desktop, and Android-based software development services. During project execution, delays often occur due to several factors, particularly in estimating the work time. These time estimates frequently encounter discrepancies because they rely on rough calculations and fail to account for both optimistic and pessimistic scenarios. Additionally, there is no system in place to determine which tasks should be prioritized and which can be postponed. To address these issues, CV. Infotech Media requires a project scheduling information system. The proposed solution utilizes the Program Evaluation and Review Technique (PERT) to calculate accurate time estimates and identify the critical path, highlighting tasks that must be prioritized and cannot be delayed. Based on the test results, the project scheduling information system successfully addresses the company's challenges by providing accurate time estimates, offering critical path information, and generating schedules in the form of a Gantt Chart.